Legal Risks of Nurses' Negligence in Interpreting Drug Prescriptions - Ananda Putri Devita; Claudia Marta Yuninda; Imelda Tune; Rustiwi Bekti Wijayanti (PT. Caesarindo Triloka Persada, 2025)
Errors in the medication administration process are a form of medication error that has the potential to jeopardize patient safety. Nurses as health workers who are directly responsible for these actions have legal, ethical, and professional obligations in their implementation. This study aims to identify the factors that cause nurses' negligence in reading drug prescriptions and examine the forms of legal risks that may arise as a result of such negligence. Qualitative descriptive method was used in this study. Various literatures, such as books, journals, and regulations, were analyzed. The study showed that medication errors can be caused by illegible prescription writing, similarity of drug names, high workload, lack of training, and lack of interprofessional coordination. The legal risks that can be imposed on nurses fall into two categories, namely administrative sanctions and criminal sanctions. Negligence in reading drug prescriptions not only risks endangering patients clinically but also poses serious legal consequences for nurses. Therefore, nurses need to carry out their duties with care and always comply with professional standards to reduce the risk of errors while protecting themselves from lawsuits.